THE INFLUENCE OF COMMITMENT ON PURCHASE INTENTION FOR LOOKE CONSUMERS IN SURABAYA - Sarah Faticha; Larasati Ayu Sekarsari (At-Tadbir : jurnal ilmiah manajemen, 2024)
This study examines the relationship between product packaging, key opinion leader effectiveness, commitment, and brand image on the purchase intention of Looke consumers in Surabaya.  The type of research used is quantitative research through a consumer survey approach. The sampling technique used was purposive sampling. Data collection is done by survey method through google form filled in by respondents. The research sample used was 156 respondents who had bought and used Looke products in the Surabaya area. In this study, the test used in statistical analysis is hypothesis testing with PLS-SEM (Partial Least Square Structural Equation Modeling) software and WarpPLS 7.0. Based on the management results, (1) Product Packaging has a significant effect on Purchase Intention; (2) Key Opinion Leader has a significant effect on Brand Image: (3) Brand Image has a significant effect on Purchase Intention; (4) Commitment has a significant effect on Brand Image; and (5) Commitment has a significant effect on Purchase Intention.